Faktor-Faktor yang Mempengaruhi Pertumbuhan Aset Bank Umum Syariah di Indonesia - Prisa Ayu Pertiwi (Journal of Applied Islamic Economics and Finance, 2021)
This research aims to influence of operational activity and non operational activity to asset growth in sharia commercial banks in Indonesia. The population of this study is Sharia Commercial Banks in Indonesia. The sampling technique uses purposive sampling which consists of Bank Muamalat Indonesia, Bank Panin Syariah, Bank Bukopin Syariah, Bank Syariah Mega Indonesia, Bank Victoria Syariah, BCA Syariah, Bank Syariah Mandiri, BRI Syariah and BNI Syariah. Data is sourced from the financial statements of each person each Islamic bank published through their websites bank. The method used is the Analysis of Poleed Data Regression with tools analysis namely Eviews. The results of this study operational activity with proxy mudharabah financing can’t have effect to asset growth. And than musyarakah financing and murabahah financing have effect to asset growth. While Non operational activity with proxy Deposits with Bank Indonesia have effect and Deposits with other comercial bank can’t have effect to asset growth sharia comercial bank